High‐dose PPI‐amoxicillin dual therapy with or without bismuth for first‐line Helicobacter pylori therapy: A randomized trial. Issue 4 (20th May 2019) - Yu, Lou; Luo, Laisheng; Long, Xiaohua; Liang, Xiao; Ji, Yingjie; Graham, David Y.; Lu, Hong
Abstract: Background: A reliably highly effective high‐dose proton‐pump inhibitor plus amoxicillin (dual Helicobacter pylori therapy) has remained elusive. We compared whether the addition of bismuth to high‐dose dual therapy would improve the efficacy of high‐dose dual therapy as first‐line treatment. Methods: This was an open‐label, randomized single‐center study of 160 treatment‐naive patients with H. pylori infection who were randomly assigned to 14‐day therapy with esomeprazole 40 mg twice a day plus amoxicillin 1 g three times a day with or without bismuth potassium citrate 600 mg (elemental bismuth 220 mg) twice a day. Antibiotic resistance was determined by agar dilution method and eradication by 13 C‐urea breath test. Results: The per‐protocol eradication rates were 96.1%; 95% CI = 88.9%‐99.2% (73/76) without bismuth vs 93.3%; 95% CI = 85.1%‐97.8% (70/75) with bismuth ( P = 0.494). The intention‐to‐treat eradication rates were 92.5%; 95% CI = 84.4%‐97.2% (74/80) without bismuth and 88.8%; 95% CI = 79.7%‐94.7% (71/80) with bismuth ( P = 0.416). Resistance to amoxicillin, clarithromycin, metronidazole, and levofloxacin was 0%, 31.7%, 81.4%, and 40.7%, respectively. Smoking reduced treatment effectiveness limited to those not receiving bismuth. The per‐protocol eradication rates were 70% (7/10) vs 100% (66/66) in smokers vs non‐smokers without bismuth ( P = 0.002), and 100% (10/10) in smokers vs 92.3% (60/65) in non‐smokers with bismuth ( P = 1.0). The adverse event rates were 7.5% (6/80) without bismuth vs 11.3% (9/80) with bismuth ( P = 0.416). Conclusions: Fourteen‐day high‐dose dual therapy was both effective and safe for first‐line treatment in a region of high prevalence antibiotic resistance. Adding bismuth only improved treatment effectiveness among smokers.